Plasma vasopressin and blood pressure. Studies in normal subjects and in benign essential hypertension at rest and after postural challenge. Issue 6 (June 1983) - Davies, R; Forsling, M; Bulger, G; Phillips, T
Abstract : Plasma vasopressin levels were compared in three groups comprising normotensive, mildly hypertensive, and more severely hypertensive patients, both under basal conditions and following an 85 degrees head-up tilt, a stimulus known to provoke vasopressin release in man. Vasopressin levels increased two- to fivefold in all subjects after tilt; however, neither the basal levels nor the maximal levels attained at 45 to 60 minutes after tilt differed in the three groups. These data do not support the postulated role for vasopressin in the causation or perpetuation of non-accelerated essential hypertension in man.